O verbo-suporte fazer na língua portuguesa : um exercício de análise de base funcionalista - Conejo, Cássia Rita (2008)
This study has the objective of observing the linguistic phenomenon named supportverb, which is used by various speakers and on many different situations of communication. As a corpus to our research we will use print interviews taken from a weekly nationwide Brazilian magazine called "Isto É". The interviews that were used refer to the months of August/2007 to January/2008 and are used because we were aiming at a middle ground between written and spoken language. This middle ground is manifested by the retextualization process used in the magazine. The only language constructions that will be looked at are the ones in which the verb "fazer" (do/make) acts as support. Our objectives are: to talk about the peculiar structure of support constructions, to establish, within a continuum, the structures with "fazer" (do/make) appearing as a plain verb, the ones regarded as fixed expressions and, afterwards, the constructions with the support-verb "fazer" (do/make) located between the two already mentioned situations. We also seek to stablish phrasal patterns to the support constructions within different degrees of prototipia and referenciality of the construction, as well as observing if there is any regularity in the verbal aspect of the construction and the meaning of it. As a path to demonstrate the pragmatic contribution of the support constructions in the building of the sentence we also want to check the functionality(ies) of the studied constructions. Some tests will be used to set the limit between the early mentioned constructions and rule out the ones which do not match with our criterion of "fazer" (do/make) as a support-verb. The current study is justified by the possible contribution represented by the documentation of constructions with support-verb, and also by the delimitation of phrasal patterns which are used in these constructions. The present paper aims to validate the hypothesis that speakers/writers of Portuguese language resource to support structure to outline more expressively, and at the same time more formally, the information which they wish to transmit.